Decission Tree Sebagai Metode Penentuan Penjurusan Perguruan Tinggi Berdasarkan Minat Dan Bakat Melalui Data Raport Dengan Uji Algoritma C4.5 (Studi Kasus di SMKN 1 Donorojo Pacitan) - Arif Baktiar (LPPM Universitas Merdeka Madiun, 2022)
The decision tree method is built using data with variable input, rapot value, gender, and age of SMKN 1 Donorojo learners with label corners. Furthermore, the concept of C4.5 algorithm became one of the techniques in the formation of decision trees. In the procedure, the selection of attributes as a branch in the C4.5 algorithm uses the calculation results of the gain ratio. Based on the concept of calculations designed, the C4.5 algorithm is used in building decision trees in providing recommendations for learners at the college level. This research will qualitatively analyze the implementation of the decision tree method in determining student direction by using the C4.5 algorithm of data mining in the form of a gain ratio of rapot values, interests and talents of students. From the results of the C4.5 decision tree algorithm test can make more accurate predictions in the research of the management of majors and major recommendations for learners. The existence of these methods is expected to be able to provide solutions for students and schools concerned in determining the appropriate majors for students to pursue to the opportunity for success and improve the ability to study in college. C4.5 algorithm itself uses an induction approach where in this approach, the C4.5 algorithm. Divide data based on the criteria selected to create a decision tree.Keywords—: Decision tree, direction determination, C4.5 algorithm